Methods for locating structural defect spots by acoustic emission signals - Babak, V. P.; Filonenko, S. F. (Proceedings of National Aviation University (archive), 2003)
A review of methods and algorithms for detecting spots of structural defects developing in products under load is given. These methods and algorithms are used in acoustic emission systems designed for locating the sources of acoustic radiation